Government by investigation : Congress, presidents, and the search for answers - PAUL C. LIGHT (Brookings Institution Press, 2013)
This book is about the 100 most significant investigations of government between 1945 and 2012. All of the investigations were designed to fix a breakdown in a government performance. In an ideal investigatory world, all 100 investigations would have asked every possible question, assessed every possible answer, and fixed the breakdown once and for all. But in the real world covered by this book, one group of investigations asked most of the questions, assessed the available answers, and mostly fixed the breakdown, while a second group muddled through to minimal effect. This book is designed to explain the differences. Every decade provided legendary investigations to the 100: Pearl Harbor and communists in government during the 1940s, and continuing with quiz shows and Sputnik in the 1950s, crime rates and the Vietnam War in the 1960s, Watergate and domestic spying in the 1970s, Social Security and the shuttle Challenger in the 1980s, Clinton misconduct and early warning about terrorism in the 1990s, and the Iraq War and financial meltdown in the 2000s. Every decade also contributed forgotten or less visible investigations: commodity speculation and government reorganization in the 1940s, airport safety and drug prices in the 1950s, White House news management and defense stockpiling in the 1960s, welfare fraud and the General Services Administration in the 1970s, Indian affairs and government mismanagement in the 1980s, Ruby Ridge and Y2K in the 1990s, and mine safety and the Solyndra loan in the 2000s.